Institutionalizing Local Narratives: Community History and Lore for Primary Grades in Dumaguete City, Philippines - Gomez-Soluta, Andrea (Silliman Journal, 2022)
This paper presents the gathered folk and historical narratives from the thirty barangays in Dumaguete City, Central Philippines contributed through the oral history method by 36 elderly natives of Dumaguete when asked to share popular local folk stories and significant events in the area within living memory as well as to recommend narratives in and about the locality that should be passed on to the young as part of their elementary school learning. Using thematic analysis, the study was able to establish the following common topics and themes running through the local narratives gathered: origin of barangay name; community spirit (with themes of peace and harmony, respect and trust); rhythm of daily life in years past (with themes of prayerfulness and hard and simple but happy life); war experience (with themes of cruelty, survival, courage, and patriotism); and ghosts and supernatural creatures (with themes of woman ghost or enchantress and malevolent creatures). The quality of the topics and themes drawn from the study’s data proves that local narratives are a very rich source of materials for the mother tongue-based History, Culture, and Values classes in elementary schools.